Analisis Kinerja Keuangan Berdasarkan Laporan Keuangan 2020-2022 pada Perusahaan PT Adhi Commuter Properti TBK (Studi Kasus BEI) - Bangkit Hamonangan Simangunsong; Dea Agung Nugraha; Kusumastuti, Ratih (CV. Kalimasada Group, 2023)
The research is intended to analyze the financial performance of the company PT Adhi Commuter Properti Tbk based on its financial statements. From the annual financial reports of PT Adhi Commuter Properti Tbk, data was obtained for the 2020-2022 period. The assessment used is the liquidity ratio, then profitability, ROA, and ROE. In addition, analysis of profit and revenue growth and cash flow is also carried out to evaluate the company's financial performance. The analysis was carried out to find out how PT Adhi Commuter Properti Tbk utilizes its financial resources in developing the property business and how the company gains profit in its business. This research provides insights for investors and decision makers to improve their company's financial performance and find out how PT Adhi Commuter Properti Tbk can utilize its financial resources effectively in its property business.